Stranger origins - Castle, Jack (Castle Books Inc., 2019)
"First came radio, then movies and television. Virtual reality only lasted until hologram-rooms became a household name. Still, the suspension of disbelief was never enough. Then...Henry Stranger revealed his full-immersion theme parks to the world, and within a single generation more people lived, worked and played in Henry Stranger Worlds than out of them. Real or imagined, historical or fantasy: it doesn't matter, pick any story-world you like. What could possibly go wrong? Hard to believe the end of the world all began in a cubicle, with a sweet, unassuming Creationeer, named Lisa Burton."-- back cover